(untitled) (Andamios, Revista de Investigación Social, 2006)
The article is a reconstruction of Max Weber’s theory of democracy. First, it specifies his notion of democracy. Later, he reconstructs the bureaucracy-politics conflict, which properly articulates politics and democratic themes in the German sociologist’s thought. Subsequently it tackles some ideas Weber maintains about State, parliament, and parties as eminently political institutions, and it emphasizes their relation with democracy. The dissertation finishes analyzing the public servant as a leader—mass relation as opposed to a parliamentary function. The résumé evaluates the extents and restrictions of Weber’s reflections to think about democracy today.